SUNAT PADA ANAK PEREMPUAN (KHIFADZ) DAN PERLINDUNGAN ANAK PEREMPUAN DI INDONESIA: Studi Kasus di Kabupaten Demak - Jauharotul Farida; Misbah Zulfa Elizabeth; Moh Fauzi; Rusmadi Rusmadi; Lilif Muallifatul Khorida Filasofa (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2017)
Female circumcision is one of the continuing practices in some countries of Africa, Europe, Latin America, and Asia, including Indonesia. In Arab, tradition of female circumcision has been widely known before the Islamic period. While in Indonesia, some areas practicing female circumcision include Java, Madura, Sumatra, and Kalimantan. This research used qualitative-ethnographic method. Data were collected through in-depth interviews to the traditional birth attendants who performed circumcision and to the baby's parents who sent their children for circumcision. In addition, Focus Group Discussion (FGD) involving medical personnel (doctors and midwives), traditional birth attendants, the parents, community leaders, religious leaders, academics, and government, was also conducted to explore the data. Then, the obtained data were analyzed by using descriptive analytical technique. The result shows that the practice of female circumcision in Demak Regency was done in 2 ways, namely symbolically and truly. Symbolically means that the practice of female circumcision was done by not cutting a female genital part, ie clitoris, but using substitute media, namely turmeric. On the other hand, the real meaning means that female circumcision was actually done by cutting little tip of the clitoris of a daughter. The time for practicing female circumcision in Demak regency was generally coincided with Javanese traditional ceremonies for infants / young children. The purpose for the daughters was in order to become sholihah and be able to control their lusts (not become